Crop productivity and the global livestock sector: Implications for land use change and greenhouse gas emissions - Havlík, Petr; Valin, Hugo; Mosnier, Aline; Obersteiner, Michael; Baker, J.S.; Herrero, Mario; Rufino, Mariana C.; Schmid, Erwin (Wiley, 2013)
The livestock sector accounts for 30% of global land area and is a major driver of land use change (Geist and Lambin 2002). Steinfeld et al (2006) calculated that deforestation due to the expansion of pasture and feed crops was responsible for 8% of total anthropogenic Co2 emissions. In addition, methane emissions from enteric fermentation and manure management accounted for 32% and 7%, respectively of agriculture sector non –Co2 emissions livestock sector will thus have large impacts on global greenhouse gas (GHG) emission levels. The objective of this paper: 1) to investigate the particular role played by crop yield increases in the dynamics of livestock production systems; 2) to explore whether these dynamics could lead to sparing of not only cropland but also grassland; and 3) to quantify the implications for related GHG emissions. Crop yield increases since 1961 have spared 85% of cropland expansion and avoided emissions of some 590 gigatons (Gt) Co2-eq in the crop sector, compared to an alternative scenario without productivity increases (Burney, Davis, and Lobell 2010). In a prospective analysis, Tilman et al.(2011) demonstrated that if the current trends of low intensification in developing regions were to continue, five times more additional cropland(1 billion ha) would be needed and three times more GHG emissions would be emitted by 2050 than improvements. However, neither of these studies considered the indirect effects of increases in crop productivity on the dynamics of the required for livestock production. Evenson and Rosegrant (2003) showed that without the improvements that took place in crop genetics between 1965 and 2000, food crop prices would have been 35-66% higher. The price reductions generated by crop yield increases should, ceteris paribus, encourage farmers to replace some of the grass in ruminant rations with crops. This would lead to land sparing and related Co2 emission reductions in regions where the feed productivity per unit of area is higher for cropland than for grassland. However, because of the multiple and complex relationships between crop, livestock and land-use, clear-cut conclusions about the direction and magnitude of change in land use and GHG emissions cannot be obtained without integrated economic modeling. In this study we implement the global partial equilibrium model GLOBIOM, which has been used extensively in the past: 1) to analyze the effects of biofuel policies on total GHG emissions balance (Havlik et al. 2011; Frank eta l. forthcoming; and Mosnier et al. 2012); 2) to assess the mitigation potential of reduced emissions from deforestation (Bottcher et al 2012); and 3) to investigate future global challenges in the sector in general.